STEM as opportunity to get TSLN right: Science education for economically productive creativity. Issue 4 (1st October 2020) - Tan, Michael
ABSTRACT: This article considers the future of STEM education in Singapore, with implications for comparable schooling systems. The Thinking Schools Learning Nation (TSLN) interventions since 1997 brought changes to science education ostensibly for economic competitiveness, the results of which can only become visible in international comparisons in this decade. I propose that TSLN represents a trade between some sacred cows of public schooling in exchange for magic beans, and I assess how well these beans have grown. In terms of economically productive creativity, the metrics present a mixed picture. Three problems that may have been overlooked could have contributed to this outcome: (i) misunderstanding the role of culture in artefact creation and use; (ii) a rational, deficit model for education; and (iii) an underestimation of the complexity of educating for economic goals. To attend to these issues, I propose a holistic vision of a STEM curriculum that recognises the social sciences of STEM as a legitimate concern for STEM educators, and a humanistic pedagogy that eschews deficit models for education. Such a vision recovers the value of the 'useless' knowledges of the humanities in STEM education, and approaches instruction with an intention towards enabling students to respond to unforeseeable futures.